Animals as the third in relational psychotherapy : exploring theory, frame and practice - Silbert, Jo; Frasca, Jo (Abingdon, Oxon ; New York, NY : Routledge, 2021)
Animals as the Third in Relational Psychotherapy: Exploring Theory, Frame and Practice elegantly and skilfully weaves together relevant literature, clinical reflections, compelling case material and contemporary psychoanalytic theory to demonstrate how the presence of an animal in the treatment arena can eventually bring about relational, interpersonal and intrapsychic change. Contemporary relational psychoanalytic literature has been virtually silent about our relationship with animals, a feature seemingly intrinsic to our relational worlds. This book seeks to remediate this void by giving voice to the practice and principles of working relationally in the presence of an animal. The text accentuates recurrent themes: animals are seen by human beings as significant subjective others and are treated as legitimate partners for relational and interpersonal processes, attachment figures and transferential objects; animals in the psychotherapy environment can play the role as a bridge' from the unconscious to the conscious, from the dissociated to the experienced, from the intrapsychic to the interpersonal; as the third in the treatment arena, the animal helps to reveal the field, bringing conflicts to life and making them available for analysis in the clinical setting. In seeking to authorise the incorporation of animals into the practice of relational psychotherapy the text applies conventional concepts to novel contexts; it extends psychoanalytic and relational principles to create a theoretical framework within which to consider the therapeutic effects of working in the triadic interactions of therapist, client and animal and thus also begins to evolve a new version of relational psychoanalytic practice. The authors value the human-animal experience in treatment and repeatedly show how the application of a relational psychoanalytic lens to the patient-therapist-animal triad can enhance the therapeutic process in ways that encourage progressive communication, understanding of the patient and the relaxing of defences, leading to the symbolising of relational capacity, therapeutic breakthrough and intrapsychic change.
OCLC-licensed vendor bibliographic record.
Keywords: Pets -- Therapeutic use; Animals -- Therapeutic use; Human-animal relationships; Psychotherapy; PSYCHOLOGY / Psychotherapy / Child & Adolescent; PSYCHOLOGY / Movements / Psychoanalysis; PSYCHOLOGY / Psychotherapy / General